10 Friend Street, 1853 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northwest of a three story wood dwelling at 10 Friend Street. To the left of the dwelling, behind an ironwork fence is a trellised garden. Jeremiah Kittredge home, demolished April 1869. Formerly a separate lane. 9 1/2 x 7 1/2 Photographs